Illness experience sharing on personal blogs: a case study of Malaysian breast cancer survivors - Wan Nur Asyura Wan Adnan; Noor Aireen Ibrahim; Nur’ain Balqis Haladin; Wan Farah Wani Wan Fakhruddin (Penerbit Universiti Kebangsaan Malaysia, 2019)
Illness experience which was very much a private matter is now increasingly becoming a shared public experience on different public spaces including social media, and other interactive online platform such as personal blogs. Past research has shown that sharing illness experience provides emotional support which surpasses traditional face to face support. In addition, studies also suggest that online sharing of illness experience can be both therapeutic as well as beneficial for cancer patients. Thus, exploring cancer discourse on media is important in enhancing understanding of the nature and characteristics of cancer discourse as constructed on social media. This is especially important in breast cancer illness, in the Malaysian context in which survival rate remains low due to lack of awareness and reluctance to perform screening. Hence, a total of three personal blogs written by breast cancer survivors from Malaysia were examined in this study. Taking a discourse analytic perspective, this study explored the positions taken by bloggers when constructing their illness experience and how these positions are realised through the different discursive strategies and linguistic devices. The findings provide insights into how breast cancer patients position themselves when they share their illness experience online. Understanding this new form of illness sharing provides an avenue to better understand breast cancer patients’ journey and their struggles, and the different roles relevant parties can play in their own health care management and information.